Aplikasi 3D Penunjang Visualisasi Penerimaan Siswa Baru Pada Gedung Madrasah Aliyah Guppi Mamuju Menggunakan Unity Engine - Hidayat Hidayat; Rahmat Rahmat; Muzdalifah Muzdalifah (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The design of a 3D map visualization application using the Unity Engine at the Madrasah Aliyah Guppi Mamuju building was carried out by creating 3D objects and then inserting them into the Unity Engine. The resulting design consists of 4 scenes, namely the Main Menu Scene, Exploration Scene, Room Select Scene, and Information Scene, where based on the implementation test results, all scenes ran well. Implement the 3D map visualization application using Unity Engine in the Madrasah Aliyah Guppi building. Mamuju is only carried out on computer devices with minimum specifications of 2.0 GHz Processor, Windows 10 Operating System, 4GB RAM, Video Card, and minimum 20GB Hard Disk.